Chicken : a collection of easy and elegant recipes. (United Kingdom : Love Food, 2007)
Chicken is an essential source of protein, B vitamins and minerals and is naturally low in fat, making it the dream food for those who need to keep their weight or cholesterol levels in check. It's not all about nutrition - there are so many wonderful ways to cook chicken that you could serve this versatile ingredient every day of the week and still not run out of ideas! This book has a selection of the best recipes from around the world.
Introduction -- Soups, starters & salads -- Lunch & light meals -- Hearty dishes -- Noodles & pasta -- Rice.
Includes index.
Keywords: COOKING -- CHICKEN